Integrated use of organic and synthetic fertilizers improves soil functioning, growth, yield and quality attributes of maize - Asif, Muhammad; Rehman, Basitur; Javaid, Muhammad Mansoor; Aziz, Ahsan; Akhtar, Naeem; Safdar, Ehsan (International Journal of Applied and Experimental Biology, 2024)
The combined use of organic and chemical fertilizers may prove to be an excellent option for maintaining soil health, increasing fertilizer use efficiency, and improving crop quality and yield of maize. So, with this objective in mind a pot experiment was conducted to find out the effectiveness of organic and synthetic fertilizers on the yield and quality of maize crop. Two organic fertilizer levels (FYM and Press-mud @ 2% and 4% of each) were tested separately and in combination with recommended NPK fertilizers (160: 80: 60 kg ha-1). The experimental units were laid out in a completely randomized design (CRD) with five replications. The results showed that the combined use of NPK + press mud @ 4% caused a significant increase in grain numbers per cob (8.6%), weight of grains per cob (11.5%), grain yield, biological yield, harvest index, stalk yield, and oil and protein contents up to 11.5%, 6.3%, 19.7%, 12.6% and 12.0%, respectively as compared to the control treatment. The oil and protein contents were also improved significantly over the sole application of NPK fertilizer. Soil health was also improved due to the combined use of synthetic fertilizer with 4% press mud and 2% FYM. It is concluded that integrated use of NPK fertilizers and press mud @ 4% not only increased the quality and yield of maize, but it also improved soil health.